Rezension von: Commission Internationale d’Histoire du Sel, CIHS-Bibliographie ... - Weber, Raimund J. (Württembergisch Franken, 1994)
Rudolf Palme (Red.), CIHS Bibliographie 2 (hrsg. vom Generalsekretariat der Commission Internationale d’Histoire de Sei (CIHS)), Schwaz (Berenkamp) 1992. 112 S. Hans Ulrich Vogel (Bearb.), Bibliography of works on salt history published in China between 1980 and 1989 (CIHS Bibliographie, Beiheft 1), Schwaz (Berenkamp) 1992. 97 S.